TRIGONOMETRIC EQUATIONS - Abdullayev Nurbek Shukhrat ogli; Yoldoshev Bekmirza Shukhrat ogli; Matkurbanov Ganjaboy Botir ogli (American Journals Publishing, 2024)
Trigonometric equations are mathematical expressions involving trigonometric functions like sine, cosine, and tangent. This book provides a comprehensive overview of trigonometric equations, covering various solution techniques and applications in mathematics and other disciplines. It offers clear explanations, examples, and exercises to help readers understand and master the concepts of solving trigonometric equations.
Keywords: Trigonometric equations, trigonometric functions, sine, cosine, tangent, inverse trigonometric functions, identities, solutions, applications, graphical methods.